Experimental study on severe plastic deformation of Ti by novel equal-channel angular pressing - Jamian, Saifulnizan; Sato, Hisashi; Fujiwara, Eri Miura; Yoshimi, Watanabe (Japan Society of Applied Physics, 2012)
This study involves experimental investigation on severe plastic deformation (SPD) of Ti using novel equal-channel angular pressing (ECAP) at ambient temperature. Ti wire is tightly encapsulated in a hollow host material made of Al-based functionally graded material (FGM). The host material is prepared by embedding Al–Al3Ti alloy into Al. Three types of the Al–Al3Ti alloys with different Al3Ti volume fractions are used to prepare the host materials. ECAP for specimens is carried out for up to eight passes by route A. The microstructure and hardness of ECAPed specimens are investigated. The changes in microstructure and the increase in the hardness value of Ti with increased number of ECAP passes are evidences showing that Ti is successfully deformed by this technique.